Technology Adoption in Inventory Management Systems: Challenges and Impact on Supply Chain Performance in Healthcare Institutions - Almanzor Jr., Lazaro A. (International Journal of Research in Interdisciplinary Studies, 2025)
This study investigates the adoption of technology in inventory management systems (IMS) and its impact on the supply chain performance of healthcare institutions. The research aims to identify the challenges healthcare institutions face in adopting IMS technologies and evaluate how these technologies influence supply chain performance. The researcher employed a descriptive-correlational research design and distributed a survey questionnaire to key personnel in selected healthcare institutions in the Philippines. Data were analyzed using statistical tools such as frequency distribution, mean, standard deviation, and correlation analysis. The findings revealed that healthcare institutions face significant challenges related to training, user acceptance, and the lack of infrastructure, which hinder effective IMS adoption. However, the study also found that successful IMS adoption leads to improved supply chain performance, including better inventory accuracy, reduced operational costs, and enhanced decision-making processes. The researcher found that these outcomes significantly improve operational efficiency in healthcare settings, leading to better service delivery. In conclusion, while the adoption of technology in IMS presents challenges, it offers considerable benefits that can enhance supply chain performance in healthcare institutions. It is recommended that healthcare institutions focus on addressing the barriers to technology adoption, particularly through training, infrastructure improvements, and fostering a culture of acceptance toward new technologies.